Evaluation of the Effects of Endodontic Materials on Fibroblast Viability and Cytokine Production - Gomes-Filho, Joao Eduardo [UNESP]; Watanabe, Simone [UNESP]; Gomes, Alessandra Cristina [UNESP]; Faria, Max Douglas [UNESP]; Lodi, Carolina Simonetti [UNESP]; Penha Oliveira, Sandra Helena (Elsevier B.V., 2009)
Introduction: Recently, a new sealer composed of Portland cement named Endo-CPM-Sealer was developed. The aim of this study was to investigate the effects of Endo-CPM-Sealer (EGEO SRL, Buenos Aires, Argentina), Sealapex (Sybron Endo, Glendora, CA), and Angelus MTA (Angelus, Londrina, Brazil) on cell viability and cytokine (interleukin [IL]-1 beta and IL-6) production by mouse fibroblasts. Methods: Millipore culture plate inserts with polyethylene tubes filled with materials were placed into 24-well cell culture plates with mouse fibroblasts. Cells cultured with only empty polyethylene tubes were used as the control. After 24 hours, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay was used to evaluate the cell viability. For cytokine assay, mouse fibroblasts were incubated in 24-well flat-bottom plates with set material disks at the bottom. Cells cultured without the material disks served as the negative control. After 24 hours of incubation, culture media were collected for cytokine evaluation by using an enzyme-linked immunosorbent assay. The data were statistically analyzed by analysis of variance and Bonferroni correction. Results: Endo-CPM-Sealer, Sealapex, and Angelus MTA did not inhibit the cell viability. All materials induced IL-6 releasing, but the amount was not statistically significant compared with the control group. Angelus MTA induced IL-1 beta releasing significantly more than the control. Conclusions: All materials were not considered cytotoxic in fibroblast culture. (J Endod 2009;35:1577-1579)
Keywords: Cell culture; cytokine; cytotoxicity; endodontic materials